Analisis Efektivitas Program Pemberdayaan Ekonomi Jemaat (Studi Kasus GMIT Imanuel SoE Tahun 2016-2021) - Irene Sondang Ully; Delci A. Tualaka; Sutry Boba Hawu (Institut Agama Kristen Negeri Kupang, 2024)
The church has a strategic role in empowering the congregation's economy, but often faces ongoing challenges. This study analyzes the GMIT Jemaat Imanuel SoE Economic Empowerment Program for the 2016-2021 period using a qualitative method with a case study approach and SWOT analysis. Data collection was carried out through in-depth interviews and document analysis with key informants from the Congregation's Economic Empowerment Service Assistance Unit. This study reveals two main programs, namely Micro Business Unit Development and Pig Fattening with revolving funds. Critical findings show a significant decrease in the rate of return on capital in both the micro business development program from 100% to 16.67%, and the pig fattening program from 62.5% to 41.76%. This study emphasizes the need for a comprehensive church economic empowerment model with a continuous monitoring mechanism and measurable risk mitigation strategies.